Role of E region conductivity in the development of equatorial ionospheric plasma bubbles - Bhattacharyya, A. (My University, 2004)
[1] A transmission line analogy, which has been used earlier in a linear theory for the development of equatorial plasma bubbles, is extended to study the effect of E region conductivity on non-linear evolution of the plasma bubbles. For this, a set of mode coupling equations are used to describe non-linear development of equatorial plasma bubbles in the presence of field-aligned currents which couple the equatorial F region with conjugate E regions. For a three mode system, these non-linear equations yield a condition for unstable fixed states. This condition shows that E region resistivity together with F region polariz-ability introduces another time scale in the non-linear evolution of equatorial bubbles, and this is the time scale for discharging the bubbles.
Keywords: Ionospheric plasma; Plasma bubbles; Equatorial ionospheric; E region